2016
DOI: 10.1186/s40064-016-3728-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of saliva microbiota’s functional feature based on metagenomic sequencing

Abstract: Objective Saliva, a mixture of exocrinally secretive fluids, amounts to ~1.5 L daily and harbors numerous microbial inhabitants. However, except the organismal structure of saliva microbiota, the functional profile of saliva microbiota remain elusive.MethodsHere we used metagenomic sequencing to experimentally reconstruct the global genomic profile of saliva by sequencing total saliva DNA from two healthy and two caries-active (DMFT ≧ 6) adults.ResultsWe found that saliva microbiota, representing 30–60% of tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 45 publications
2
14
0
Order By: Relevance
“…They found the metagenome of the healthy individuals to be enriched with genes involved in anti-bacterial functions relative to that of the caries-affected individuals. This difference in the health and caries metagenome was also found in a study of four individuals [35]. These metagenomic studies, due to their small sample size, cannot determine the degree of inter-individual variation, nor predict whether it will be large, as seen in16S analyses.…”
Section: Composition Versus Functionmentioning
confidence: 82%
See 2 more Smart Citations
“…They found the metagenome of the healthy individuals to be enriched with genes involved in anti-bacterial functions relative to that of the caries-affected individuals. This difference in the health and caries metagenome was also found in a study of four individuals [35]. These metagenomic studies, due to their small sample size, cannot determine the degree of inter-individual variation, nor predict whether it will be large, as seen in16S analyses.…”
Section: Composition Versus Functionmentioning
confidence: 82%
“…Recent genetic research of the oral microbiome has indicated that the 'what are they doing?' approach of assessing functional differences between health and caries may be more clinically relevant [34,35]. The function of the oral microbiome can be assessed by directly sequencing the majority of DNA present in a sample, capturing the vast array of different genes from the different bacterial species.…”
Section: Composition Versus Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…The collected plaque was put into a 1.5 ml centrifuge tube containing 1 ml PBS solution. Saliva was collected using method described by Fang Yang et al [26], an amount of 2.5-3 ml saliva was collected. All collected samples were immediately stored in a refrigerator at -20℃ before laboratory analysis.…”
Section: Collection Of Plaque and Saliva Before Sdf Interventionmentioning
confidence: 99%
“…The collected plaque was put into a 1.5 ml centrifuge tube containing 1ml PBS solution. Saliva in the amount of 2.5-3 ml was collected using the spitting method described by Fang Yang et al [26]. All collected samples were immediately stored in a freezer at -20℃ before laboratory analysis.…”
Section: Collection Of Plaque and Saliva Before Sdf Interventionmentioning
confidence: 99%